Knowledge and the Mystery of Black Boxes: The Construction of a Techno-scientific-culture in The Case of Digital Maritime Safety - Dicky Rezady Munaf; Yasraf Amir Piliang (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Unair, 2018)
The growth of knowledge in an institution is highly determined by the cultural system and environment, in which the knowledge is produced, disseminated and appropriated. Knowledge, which is substantially demanded for the continuation of the institution, can only be systematically generated in a good social and cultural environment. Yet, in many cases, there is a kind of “black box” that structurally impedes the production of knowledge, because of incapability of the system in constructing a collective “scientific culture”. This paper analyze the techno-scientific system usage in the Indonesia Maritime Security Coordinating Board (IMSCB) worked from 2006-2014. Here, two related systems are responsible for the production of knowledge in the institution, i.e., “techno-science” and “techno-culture”. Yet, the capacity of certain institutions in generating useful knowledge is highly determined by the capability of “techno-scientific-culture” to open “black boxes”, that is capable to reveal and understand the complexity behind natural or social realities: earthquake, Tsunami, flood, traffic jam, chaos or mass violence. Thus a cultural transformation has to be systematically initiated to integrate techno-science and techno-culture, create self-reflectivity of the scientific world, and build “public awareness” about the function, significance and science benefit and technology for community, society and humankind in general.